STUDY OF WATER HAMMERS IN THE FILLING OF THE SYSTEM OF PRESSURE COMPENSATION IN THE WATER-COOLED AND WATER-MODERATED POWER REACTORS - A. V. Korolyev; A. P. Ishchenko; О. P. Ishchenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2017)
The research presented in the article conforms to the severe accident that took place at the Three Mail Island nuclear power plant in the USA. The research is focused on improving the reliability of the pressure compensator that is an important equipment of the primary circuit. In order to simulate such a situation, the stand has been developed to simulate the design of the pressurizer of the PWR-440 reactor, in particular an elliptical shape of the upper lid which has a steam outlet pipe at the top of the construction that creates conditions for occurrence of such water hammers. For the experiments, an installation has been created that makes it possible to measure and record the water hammering that occur when the tanks are filled. Measurement of the amplitude of the water hammering was carried out by a specially developed piezoelectric sensor, and the registration – by a light-beam oscilloscope. The technique of carrying out the experiment is described and the results of an experimental study of the water hammers arising when the vessels are completely filled are presented. Quantitative data were obtained on the amplitudes of the hydraulic impacts depending on the rate of filling of the vessel and the diameter of the outlet, the maximum pressure of the hydraulic shock was 7–9 atm. Comparison of calculated and experimental data has been performed. The allowable discrepancy is explained by the calculated value of the system stiffness coefficient, which did not take into account the presence of welded seams in the tank that imparts the system with additional rigidity. The calculated relationships are obtained, that make it possible to estimate the amplitudes of the water hammers through the acceleration of the water level in front of the outlet from a vessel with an elliptical bottom. The possibility of a water hammer in the pressure compensator is demonstrated by experiment and by theoretical calculations. Based on the experimental data, a list of initial events of severe accidents at NPPs with a water-cooled and water-moderated power reactor can be expanded.